Deteccion de nematodos parasitos en material vegetal importado al Uruguay - Casella, E.=700 1 Olmos, I.; De Leon, L.; Fernandez, J.
(En, Es)
ilus., 11 ref.
Keywords: CUARENTENA; APHELENCHOIDES FRAGARIAE; MELODOIGYNE HAPLA; PRATYLENCHUS; TYLENCHULUS SEMIPENETRANS; ESPAÑA